(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
This paper offers an in-depth discussion about the theory of migration, change in livelihood, and development. Using a qualitative literature review method, this paper reviews scholarly literature chosen from both national and global sources with an emphasis on the theories in migration. This paper is mainly concerned with important theories of migration, including the neoclassical and push and pull theories, functionalism approach, historical-structural and Marxist theories, and contemporary theories trying to move away from economics in explaining migration. It is found that migration theories have always been influenced more by economic assumptions, considering migration a rational process based on spatial inequalities. Although historical-structural theories have been useful in giving us a critical perspective regarding power and uneven development, it too is still heavily based on economics. A key area in which the literature is weak in theoretical consideration is the aspect of socio-cultural values, identities, hopes, and changing attitudes influencing livelihoods of the people and migration. Contemporary theories have also added much to the discussion, although they need further theorization and conceptualization. This article makes an important contribution to migration studies through a systematic review and synthesis of existing theory. The analysis of existing gaps and conceptual problems within mainstream theories demanded to quest of more holistic approaches to understanding migration through socio-cultural dimension or social context.